The Evaluation of Output Convergence in Several Central and Eastern European Ccountries - Simionescu, M. (Ekonomika, 2015)
The main objective of this study is to check the convergence in output for six countries from Central-Eastern Europe that are also members of the European Union. A slow convergence was obtained only for Greece during 2003–2012, for the rest of the countries (Bulgaria, Croatia, Hungary, Poland and Romania) the divergence being observed. The regression coefficients were estimated using bootstrap simulations in order to solve the problem of a small data set. However, the graphical representations suggested a convergence for Bulgaria and Romania, the assumption proved also by the application of the Augmented Dickey Fuller unit root test. There is no evidence of the convergence of each country towards Greece, this country having a specific evolution of its GDP with higher values than the rest of the countries.
Keywords: convergence; GDP per capita; ADF tests; co-integration; steady state